The Effectiveness of Generative Learning Model in Enhancing Students' Science Competence: A Meta-Analysis (2015-2024) - Ahzari, Serli; Akmam, Akmam; Mufit, Fatni; Novitra, Fuja (IJIS Edu : Indonesian Journal of Integrated Science Education, 2026)
This meta-analysis examined the effectiveness of the generative learning model in enhancing students’ science competence across educational levels from 2015-2024. Analysis of studies revealed high effectiveness across elementary (ES=1.11), junior high (ES=1.18), and senior high school (ES=1.02) levels. The model showed the most potent effects in teaching Work and Energy (ES=4.07), Newton’s Laws (ES=2.90), and Light (ES=1.67). Regarding student competencies, the model was most effective in developing Generic Physics Skills (ES=4.07), Concept Mastery (ES=1.75), and Science Process Skills (ES=1.67) while showing moderate effects on critical thinking and problem-solving abilities. Results indicate that the generative learning model is particularly effective for teaching conceptual physics topics and developing practical skills, though its impact varies across different learning outcomes and subject areas.